2021
DOI: 10.1155/2021/5077886
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Dentistry on Twitter: Benefits and Dangers

Abstract: Objectives. The demand for esthetic dentistry is growing, and social media constitute the main driving force behind this revolution. Twitter is a leading social media platform; however, there is a lack of research on the pattern of communications and the impact of Twitter on esthetic dentistry. The purpose of this study was to analyze the content of tweets related to esthetic dentistry and to investigate how Twitter has affected the perception of, and demand for, esthetic dentistry. Moreover, it aimed to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This percentage is in accordance with the study conducted by Salim et al, where 57% of dentists reported posting affirmative content related to aesthetic dentistry. Further, 37% of dentists reported that they did not post content on social media because of the lack of time while a few said that it was due to ethical concerns, which is in accordance with the study conducted in the Kingdom of Saudi Arabia (KSA) where dentists stated similar reasons for not posting content related to dentistry on their social media platform [ 30 ]. In addition, the majority of dentists (90%) observed a rise in demand for aesthetic procedures in their dental practice which is in accordance with a study conducted in the Gulf region where (53%) of the patients were following a dentist or a dental clinic on social media, and they significantly agreed that dentists should communicate with people through social media rather than conventional media.…”
Section: Discussionsupporting
confidence: 73%
“…This percentage is in accordance with the study conducted by Salim et al, where 57% of dentists reported posting affirmative content related to aesthetic dentistry. Further, 37% of dentists reported that they did not post content on social media because of the lack of time while a few said that it was due to ethical concerns, which is in accordance with the study conducted in the Kingdom of Saudi Arabia (KSA) where dentists stated similar reasons for not posting content related to dentistry on their social media platform [ 30 ]. In addition, the majority of dentists (90%) observed a rise in demand for aesthetic procedures in their dental practice which is in accordance with a study conducted in the Gulf region where (53%) of the patients were following a dentist or a dental clinic on social media, and they significantly agreed that dentists should communicate with people through social media rather than conventional media.…”
Section: Discussionsupporting
confidence: 73%
“…Dentists and dental hygienists comprised 55% of these hosts [3]. The use of multiple platforms by the same host has also been reported in many previous studies [3,6,7,15,20]; how- ever, the advantages and disadvantages of a single host using multiple accounts have not been previously reported. The same study [3] also stated that hosts varied in how regularly they posted.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study on Twitter posts revealed that 56.53% of posts were related to esthetic dentistry, out of which only 5.5% was educational content. The majority of the posts were advertisements and personal highlights [ 6 ]. Abu-Ghazaleh et al [ 7 ] also presented similar results in a study on dental trauma in social media, finding that 56.2% of the posts on Facebook were advertisements.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter also increases the number of persons that can participate in medical discourse, allowing multiple medical professionals to share their expertise on a “level playing field”, and allowing for rapid dissemination of new biomedical research findings [ 10 ]. Twitter (X) has been used in dentistry/oral surgery to promote oral health behaviors, to disseminate evidence based practices via chats and journal clubs, and to disseminate information about cosmetic dentistry [ 11 , 12 ]. Many nurses used Twitter (X) extensively during the COVID-19 pandemic to highlight their difficult working conditions, to advocate for needed resources, and to convey personal and emotional experiences from their work [ 13 ].…”
Section: Discussionmentioning
confidence: 99%